Geoscience spillover:Gunnar Böðvarsson and the adoption of petroleum technologies in Iceland's geothermal industry, 1940s-1970s - Melsted, Odinn (History and Technology, 2024)
During the twentieth century, Iceland became a leader in geothermal energy use, with hot water and steam providing for the heating of 9 out of 10 houses and almost one-third of the electricity supply. A crucial factor in the expansion of geothermal energy between the 1940s and 1970s were indirect ‘spillovers’ from the oil industry via the applied geosciences. While fundamentally different in end use, geothermal and hydrocarbon industries employ similar geoscientific methods for exploring and extracting fluids and gases. This article traces the spillovers from oil to geothermal by examining Iceland’s Geothermal Division and its founding director, Gunnar Böðvarsson. He saw the oil industry as a model and embraced its geoscientific exploration methods, oilwell rotary drilling and petroleum reservoir engineering. Adapted to the requirements of geothermal energy, petroleum technologies greatly improved the knowledge of geothermal reservoirs and the efficiency of well drilling and hot water and steam extraction. The geoscience spillover between oil and geothermal reveals an understudied dimension of geothermal history and the crucial role of the geosciences at the intersection of academia and energy industries, which also resulted in reverse spillovers from geothermal to oil and complicates the common dichotomization of fossil fuels vs. renewable alternatives.